Effectiveness and Efficiency of Improving HIV Service Provision for Key Populations in Nicaragua - Broughton, Edward Ivor; Nunez, Oscar; Arana, Rafael; Oviedo, Alexey (Frontiers in Public Health, 2016)
Objective HIV in Nicaragua is concentrated among key populations (KPs) – men who have sex with men, female sex workers and female transgender – in whom prevalence is 600-4 000 times higher than the general population. The USAID PrevenSida Project is aimed at increasing healthy behavior among KPs and people with HIV and improving testing, counseling, and continuity of prevention and treatment by building capacity and improving performance of non-governmental organizations (NGOs) providing services to KPs. We evaluated the cost-effectiveness of PrevenSida’s activities. Methods This retrospective observational evaluation used individuals in KPs covered by NGOs receiving assistance from PrevenSida from 2012 to 2014. Cost-effectiveness analysis compared PrevenSida’s intervention with business-as-usual. Model inputs were generated from epidemiological modeling and PrevenSida’s records. Results By 2014, 24 NGOs received grants and technical assistance from PrevenSida with 72 955 people in KPs served at 11.32/person (9.39 to 16.55/person depending on region). The estimated incremental cost-effectiveness ratio was 50 700/HIV case averted or 2 600/Disability-adjusted Life Year (DALY) averted (95% CI: 1 000-99 000 and 50-5 100, respectively). Conclusion PrevenSida distributed about 600 000 in grants and used 230 000 to support 24 NGOs in 2014. Cost-effectiveness from the program perspective compared to no program was slightly over half of GDP per capita per DALY averted, considered highly cost-effective by WHO criteria. Cost and efficiency varied by region, reflecting the number of people in KPs receiving services. Cost-sharing by NGOs improved cost-effectiveness from the program perspective and likely promotes sustainability. Focused interventions for KP service provision organizations can be acceptably efficient in this setting.